Tiny thoughts on respect - Bezenac, Agnes; Bezenac, Salem (Beirut Dar al Maaref bookshop, 2020)
encouraging children to thing a bout the ways they treat others and understanding that with respect things often work out better for everyone
Education
For children from 3 to 6 years old
1
Keywords: Educational psychology